Ревизия рода ковалевскиелла — Kowalewskiella Васzуnska, 1914 (Cestoda, Cyclophyllidea). Сообщение II - Корнюшин, В.В. (Вестник зоологии, 1970)
В работе приводятся подробные оригинальные описания и даются
рисунки всех трех видов: К. longiannulata Baczynska , 1914, К. cingulifera
(К г a b b е, 1869), К. stagnatilidis (Burt, 1940), сохраненных автором в составе рода Kowalewskiella после его ревизии (сообщение I). Данные получены при изучении коллекции цестод, обнаруженных
у куликов Северо-Западного Причерноморья. Для каждого вида указаны
хозяева, время и место обнаружения, экстенсивность и интенсивность инвацзи The detailed original descriptions and pictures are presented of all three species, preserved by the author in the composition of the Kowalewskiella genus after its revision (communication I)— K. longiannulata Baczynska, 1914; K. citigulifera (Krabbe, 1869) and K- stagnatilidis (Burt, 1940). The data are obtained when studying the collection of cestodes, found in snipes of the north-western Black Sea area. Hosts, time and place of finding, extensity and intensity of invasion are mentioned for each species.